Meneguhkan Pancasila sebagai Rumah Bersama Semua Umat Beragama - Ahmad Salehudin (UIN Sunan Kalijaga Yogyakarta, 2011)
It is important to note the rising of religious violence and the dialectic of certain groups to alter Pancasila as the state ideology and foundation either using violent ways or abusing the triumph of democracy. Religious violence and efforts to alter Pancasila with other ideology serve as a vivid thread to the unity of The Republic of Indonesia, human right’s violation to Indonesian people carried out rituals that based on belief and religion, and the cause of self-identity uproot as a nation held bhineka tunggal ika. This paper tries to discuss some efforts to revitalize Pancasila being the house of many religions. The effort to revitalize Pancasila can be done situating it as a working ideology. Gaining this position as a working ideology, it is also urgent— besides changing the way to elaborate Pancasila values— to internalize the soul of Pancasila as ways of thinking and guiding to all Indonesian people. In this respect, Pancasila could serve as the house of many religions.